2019
DOI: 10.1186/s13104-019-4790-2
|View full text |Cite
|
Sign up to set email alerts
|

Occupational hazards in medium and large scale industrial sectors in Sri Lanka: experience of a developing country

Abstract: ObjectiveOccupational hazards is an area where many countries have begun to pay more emphasis as it affects the health of many particularly in developing countries. However, documented literature is scarce in this regard although occupational hazards are common in workplaces. The study was carried out with the objective of describing the physical hazards and control measures adopted in the formal medium and large-scale industrial sector in Sri Lanka.ResultsOf the 69 units of the 25 factories, physical hazards … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
1
9
1
Order By: Relevance
“…In all five industries, noise was the most common occupational hazard, reported by 60.4% of study subject. In accordance with the present results, a previous study reported that noise was one of the most frequent occupational hazards reported by 78.3% (15). Additionally, 34% of the factories and 27.4% of the participants respectively produced a high level of noise (16,17).…”
Section: Discussionsupporting
confidence: 93%
“…In all five industries, noise was the most common occupational hazard, reported by 60.4% of study subject. In accordance with the present results, a previous study reported that noise was one of the most frequent occupational hazards reported by 78.3% (15). Additionally, 34% of the factories and 27.4% of the participants respectively produced a high level of noise (16,17).…”
Section: Discussionsupporting
confidence: 93%
“…However, the manufacturing, utilities, agriculture and trade sectors are often cited as the most hazardous [10], compared to office-based work associated with community service and finance. Employees at these industries are often exposed to physical, chemical and biological occupational health hazard types [10,19,[72][73][74][75], which are all linked to the ODs in Table 1. The paucity of the Compensation fundderived OD and injury statistics complicates the process of attributing the specific sectors from which these accidents emanated.…”
Section: Employment and Exposure Trends In South Africamentioning
confidence: 99%
“…On this point, a survey carried out by local health inspectors in Estonia revealed that 16% of industrial workers were exposed to chemical, physical and biological agents [19]. Physical hazards and hazardous chemical substances were also identified in an occupational hygiene survey of 99 small Finnish workplaces [73] and Sri Lankan medium-and large-scale industrial sectors [72]. The extent of these hazards varies depending on the industry type, locality and precautionary measures taken by the worker and the employer [107][108][109].…”
Section: Occupational Health Hazards Exposure and Latencymentioning
confidence: 99%
“…Compared with other industries, construction is a perilous field owing to its distinctive nature (Jannadi & Buhamsin, 2002) and construction is normally categorized as high risk (Arnold, et al 2019) and historically, it has been associated with a high rate of injuries and high rates of employees' death (Chan, 2011). The Labor Department in Sri Lanka states that 500,000 man-days are lost every year owing to occupational health hazards.…”
Section: Introductionmentioning
confidence: 99%
“…Evident to this, Dharshana (2017) points out that the workplace health and safety have not yet been sufficiently addressed by the Ministry of Health, Nutrition and Indigenous Medicine. Arnold et al (2019) also clearly highlights, the occupational hazards have been identified by many countries as a major cause for the health of many developing countries, yet the documented literature is scarce. This shows the insufficient literature within the study context to explain how the management of hazardous factors affect the health and safety of the workers, especially in the construction industry.…”
Section: Introductionmentioning
confidence: 99%